Conditioned Food Aversions: Illness-Induced Aversions to the Interaction of Gustatory and Nongustatory Cues - Ihrig, Laurie H. (My University, 1980)
Laboratory rats were habituated to drinking sucrose in one environment (the sucrose environment) and water in a second (the water environment). Subjects poisoned after drinking sucrose in the water environment subsequently exhibited a marked reduction in sucrose intake in the water environment. The same subjects did not exhibit depression of water consumption in the water environment and showed only a slight, nonsignificant reduction of sucrose intake in the sucrose environment. These results indicate that rates will form an aversion to a compound stimulus consisting of both gustatory and environmental components without forming an aversion to either the gustatory or environmental component in isolation.
Keywords: Psychology; Psychology